BİR FİZYOTERAPİ ROBOTUN DİNAMİĞİ VE KONTROLÜ - KILIÇERKAN, EFRAİM (Fırat Üniveristesi, 2013)
Bu proje ile fizyoterapistlere rehabilitasyon sürecinde yardımcı olmak üzere, alt uzuvların rehabilitasyonuna yönelik bir robot kolunun tasarımı, ve kontrolü amaçlanmıştır. Proje kapsamında üç serbestlik derecesine sahip, diz için fleksiyon ekstansiyon kalça için fleksiyon ekstansiyon ve abduksiyon adduksiyon hareketlerini gerçekleştirebilen, uzuv boyutuna göre ayarlanabilen bir mekanizma tasarlanmıştır. Tasarlanan sistemin kontrolü için bilgi ve kural tabanlı çalışan, kontrol algoritmaları yapısı geliştirilmiştir.Kontrol teknikleri olarak rehabilitasyon amaçlı robotlar için PID, Bulanık Mantık ve Adaptiv PID Tip Bulanık Mantık Denetimleri teknikleri kullanılmıştır. Anahtar Kelimeler: Rehabilitasyon Robotlar, Fizyoterapi, Kontrol, Adaptiv Kontrol

With this Project, it was aimed to design and control the robot-arm to be used in lower extremity rehabilitations with purpose of helping the physiotherapists in rehabilitation process. Within the scope of Project, a mechanism with 3 degrees of freedom, and being able to perform "flexion-extension" movements in knee, "flexion-extension" movements and "abduction-adduction" movements in hip and being able to be adjusted in length was designed. For controlling the designed system, the control algorithms structure working information- and rule-based was developed. As control techniques, PID, fuzzy logic, and Adaptive PID type Fuzzy Logic Management techniques were used for rehabilitationpurposed robots. Key Words: Rehabilitation Robots, Physiotherapy, Control, Adaptive Control
Dynamics and controls of a physiotherapy robot
Keywords: Makine Mühendisliği; Fizyoterapi ve Rehabilitasyon